The impact of the micronutrient iodine in health and diseases. Issue 6 (26th March 2022) - Opazo, Ma. Cecilia; Coronado-Arrázola, Irenice; Vallejos, Omar P.; Moreno-Reyes, Rodrigo; Fardella, Carlos; Mosso, Lorena; Kalergis, Alexis M.; Bueno, Susan M.; Riedel, Claudia A.
Abstract: Adequate iodine nutrition is crucial for all mammals by playing his starring role as a component of thyroid hormones, which are key regulators of cellular processes for life such as differentiation, growth, function, and metabolism. Deficiency or excess of iodine in the diet are worldwide highly frequent conditions that are responsible of health problems like hypothyroidism, hypothyroxinemia, goiter, thyroiditis, hyperthyroidism, and autoimmune thyroid diseases among others. The incorporation of iodine in salt or other nutrients resolved the consequences of severe iodine deficiency like goiter, cretinism. However, this strategy in several countries led to other ailments like Hashimoto autoimmune thyroiditis, hyperthyroidism, and hypothyroidism. The goal of this review is to analyze and discuss the different aspects of iodine nutrition for human health comprising its biological role through thyroid hormones, pathogen control, and the regulation of the intestinal microbiota.